Nesfatin-1 treatment preserves antioxidant status and attenuates renal fibrosis in rats with unilateral ureteral obstruction - ÇETİNEL, ŞULE; YEGEN, BERRAK; KAYA, ÖZLEM TUĞÇE; ÖZBEYLİ, DİLEK (My University, 2022)
Background Nesfatin-1 (NES-1), an anorexigenic peptide, was reported to have anti-inflammatory and anti-apoptotic actions in several inflammation models. Methods To elucidate potential renoprotective effects of NES-1, unilateral ureteral obstruction (UUO) was induced in male Sprague Dawley rats by ligating left ureters. The rats were injected intraperitoneally with either saline (SL) or NES-1 (10 mu g/kg/day) for 7 or 14 days (n = 8 in each group). On the 7th or 14th day, obstructed kidneys were removed for the isolation of leucocytes for flow-cytometric analysis and the assessments of biochemical and histopathological changes. Results Opposite to glutathione levels, renal myeloperoxidase activity in the SL-treated UUO group was significantly increased compared with the sham-operated group, while NES-1 treatment abolished the elevation. The percentages of CD8+/CD4+ T-lymphocytes infiltrating the obstructed kidneys were increased in the SL-treated groups but treatment with NES-1 did not prevent lymphocyte infiltration. Elevated tumour necrosis factor-alpha (TNF-alpha) levels in SL-treated UUO group were decreased with NES-1. Although total degeneration scores were similarly increased in all UUO groups, tubular dilatation scores were significantly increased in UUO groups and lowered by NES-1 only in the 7-day treated group. Elevated interstitial fibrosis scores in the SL-treated groups were decreased in both 7- and 14-day NES-1 treated groups, while alpha-smooth muscle actin (alpha-SMA) and apoptosis scores were depressed in both NES-1 treated groups. Conclusion The present data demonstrate that UUO-induced renal fibrosis is ameliorated by NES-1, which appears to involve the inhibition of neutrophil infiltration and thereby amelioration of oxidative stress and inflammation. These data suggest that NES-1 may have a regulatory role in protecting the kidneys against obstruction-induced renal injury.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; TRANSPLANTASYON; Klinik Tıp; Klinik Tıp (MED); ÜROLOJİ VE NEFROLOJİ; TRANSPLANTATION; CLINICAL MEDICINE; Clinical Medicine (MED); UROLOGY & NEPHROLOGY; Üroloji; Transplantasyon; Urology; Transplantation; apoptosis; inflammation; nesfatin-1; oxidative stress; unilateral ureteral obstruction; BLOOD-BRAIN-BARRIER; PROGRESSIVE FIBROSIS; EXPRESSION; INJURY; NEPHROPATHY; DAMAGE; ANTAGONIST; APOPTOSIS; BLOCKADE